Mathematics education research in Indonesia: A scoping review - Andi Saparuddin Nur; Inggrid Marlissa; Kamariah Kamariah; Markus Palobo; Widya Putri Ramadhani (Beta: Jurnal Tadris Matematika, 2021)
[English]: This scoping review aims to examine mathematics education research in Indonesia in the last seven years. A search on top 1 and 2 journals, which were selected through a national database (Sinta), yielded 595 articles published from 2015 to March 2021. A content analysis of the articles revealed that research mostly used by mathematics education researchers in Indonesia was qualitative (41.85%), quantitative (32.94%), and developmental (17.82%). The research participants were dominated by junior high school students (35.63%), college students or pre-service teachers (23.87%), and senior high school students (17.48%). The number of participants ranges from 31 to 60 (26.72%) in the majority of the research. Most of the research data were collected through tests, interviews, and questionnaires. Meanwhile, in analyzing the data, the use of descriptive statistics, qualitative methods, and t-tests were obtrusive. There are twelve most researched topics in Indonesia, including mathematical ability (27.23%), technology application (13.28%), and cognitive process (9.92%). Several topics that have not been developed in Indonesia are philosophy and history of mathematics education, early childhood mathematics learning, and topics on multicultural, multilingualism, and equity in mathematics education. Meanwhile, the integration of Islamic values ​​in teaching and learning mathematics is a particular topic in Indonesia. [Bahasa]: Penelitian ini bertujuan untuk mengkaji penelitian pendidikan matematika di Indonesia dalam tujuh tahun terakhir. Pencarian pada jurnal level 1 dan level 2, yang dipilih melalui basis data nasional (Sinta), menghasilkan 595 artikel yang diterbitkan dari tahun 2015 sampai Maret 2021. Hasil konten analisis dari artikel tersebut menunjukkan bahwa penelitian paling banyak digunakan peneliti pendidikan matematika di Indonesia adalah kualitatif (41,85%), kuantitatif (32,94%), dan pengembangan (17,82%). Partisipan paling banyak dilibatkan adalah siswa SMP (35,63%), mahasiswa atau calon guru (23,87%), dan siswa SMA (17,48%). Sebagian besar jumlah sampel yang digunakan berada pada kisaran 31-60 orang (26,72%). Pengumpulan data banyak dilakukan melalui tes, wawancara, dan kuesioner. Sementara itu, analisis data paling banyak menggunakan statistik deskriptif, metode kualitatif, dan uji-t. Terdapat dua belas topik paling banyak diteliti di Indonesia, diantaranya; kemampuan matematis (27,23%), aplikasi teknologi (13,28%), dan proses kognitif (9,92%). Beberapa topik yang belum banyak berkembang di Indonesia yaitu filosofi dan sejarah pendidikan matematika, pembelajaran matematika anak usia dini, dan topik terkait multikultural, multilingual, dan kesetaraan dalam pendidikan matematika. Sementara itu, integrasi nilai-nilai Islam dalam pembelajaran matematika merupakan topik penelitian yang menjadi ciri khas di Indonesia.